Maternity patients' perceptions of staff compliance with hand hygiene and skin-to-skin contact with a newborn - Lewis, Lucy; Hauck, Yvonne; Ashton, E.; Engelbrecht, D.; Nicolaou, L.; Crichton, C.; Spence, M. (Ten Alps Publishing, 2016)
© 2016 The Royal College of Midwives. Background. Hand hygiene is important in reducing community-associated infection. Placing a newborn on a mother's bare chest or abdomen (skin-to-skin) following birth promotes breastfeeding and infant health. Aim. The researchers investigated perceptions of maternity patients in relation to midwives' and obstetricians' compliance with two obstetric quality improvement outcomes: hand hygiene and skin-to-skin contact with a newborn. Design, setting and participants. This retrospective cohort study was performed at the sole public tertiary maternity hospital in Western Australia. Two questionnaires were administered: one surveyed 155 women around hand hygiene compliance and the second surveyed 163 women around skin-to-skin practices. Frequency distributions and univariate comparisons were utilised. Outcome. Women's observations of their healthcare professional's hand hygiene practices before touching the woman or her baby and their perception of skin-to-skin with their newborn, especially in the first hour following birth. Additionally, six knowledge statements around both topics were presented for agreement or disagreement. Results. A total of 153 (99%) women completed the hand hygiene questionnaire and 159 (97%) completed the skin-to-skin questionnaire. Most midwives (93%) and obstetricians (85%) were observed to wash their hands. Compared to women having a vaginal birth, those who had a CS were less likely to have early skin-to-skin contact (69% versus 97%, P<0.001), or skin-to-skin continuously for one hour or more in the first hour of their newborn's life (21% versus 56%, P<0.001). Conclusions. There is value assessing patient-centric perceptions of compliance with quality improvement outcomes. Compliance of early, sustained skin-to-skin may require innovative changes. We suggest much can be learned from the success of hand hygiene innovations, especially utilising clinical champions.